Exploring Educational Policy Innovations and Curriculum Development in Indonesian Higher Education: A Systematic Review - Rosidin, Asep; Sudirman, Sudirman; Mufti, Mohamad Irfan; Pramono, Susatyo Adhi; Susanty, Lela; Dudin, Achmad; Ernawati; Arifin, Ardian (Journal of Education Culture and Society, 2025)
Aim. This study examines the implementation of Indonesia’s Merdeka Belajar curriculum in higher education, focusing on analysing educational policy and curriculum related to this initiative. The research aims to understand how the curriculum empowers students to choose their learning paths and address challenges related to disparities in resources and facilities across institutions. Methods. Conducted through a systematic review, this research comprehensively reviewed literature from databases such as CINAHL, Pubmed, Google Scholar, and Scopus. Specific keywords like "educational policy," "Merdeka Belajar," "students," and "higher education" were used to identify relevant articles. The study analysed 20 articles to gain insights into the educational policy and curriculum aspects of Merdeka Belajar in higher education. Results. The findings underscore the importance of customising education policies to recognise students’ rights and empower them to explore their potential through the Merdeka Belajar curriculum. While the curriculum aims to enable students to choose their learning paths, challenges such as disparities in resources and facilities exist across institutions. It emphasises the need for thorough implementation reviews and adequate resources to promote equity and prevent disparities. Conclusion. This study contributes to the existing body of knowledge by providing insight into the implementation of the Indonesian Independent Learning curriculum in higher education. Its originality lies in its focus on the analysis of education policy and curriculum aspects related to this initiative, especially in addressing challenges such as resource and facility gaps.